Review of Senopterina Macquart (Diptera, Platystomatidae) from Brazil, with description of two new species - Rodrigues, João Paulo Vinicios; Carvalho, Claudio José Barros De; Mello, Ramon Luciano (Zootaxa, 2024)
A review of Senopterina Macquart, 1835, a Nearctic and Neotropical genus with 21 species, is presented. Senopterina brevipes (Fabricius, 1805), the type species of the genus, and S. macularis (Fabricius, 1805), are redescribed. Two new species are listed for Brazil: S. canina sp. nov., and S. flavifemoris sp. nov., from the following states: Amapá, Goiás, Maranhão, Mato Grosso, Mato Grosso do Sul, Paraná, Rondônia and Tocantins. SEM images of the male and female terminalia of the redescribed species and of the new species are presented. An updated identification key to species is also provided.